Determination of Lead in the Absence of Supporting Electrolyte Using Carbon Fiber Ultramicroelectrode Without Mercury Film - Da Silva, Sonia Maria (My University, 1998)
The determination of lead ions directly in water, for application in analysis of samples of environmental interest, was studied by electroanalytical techniques. Linear sweep anodic stripping voltammetry with a carbon fiber disk ultramicroelectrode (7.0 μm in diameter), without mercury film, has been used for lead determination, by standard addition, in purified water in the absence of supporting electrolyte. The response was linear in the range from 10.0 to 50.0 μg L-1, with a detection limit of 0.8 μg L-1, for 300 s preconcentration time, at -1.2 V and 1.0 V s-1 scan rate. The reliability of the analytical procedure was evaluated by precision using relative standard deviations (5.6%, for three repetitive stripping current measurements of solution with 10.0 μg L-1 lead ions) and by the accuracy with recovery experiments (mean of 110.8%) for the same concentration.
Keywords: Lead; Ultramicroelectrodes; Voltammetry; Water